1977
DOI: 10.1002/pen.760171003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of coupling agents on the mechanical and rheologica properties and mica‐reinforced polypropylene

Abstract: Dimethylaminoethyl methacrylate (DMAEMA) was investigated as a prospective coupling agent for mica-reinforced polypropylene. Composites prepared with the widely-used silane coupling agent, N-(4-vinylphenyl) methyl-N'-(3-trimethoxysilylpropy1)ethylenediamine monohydrochloride (2-6032), were compared with the amino-coupled composite. Improvements in the flexural properties at room temperature were observed with the two coupling agents: a 22 percent increase in the strength with the silane compared to a 16 percen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
1

Year Published

1990
1990
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(32 citation statements)
references
References 5 publications
4
26
1
Order By: Relevance
“…Thus, particle orientation predominates at low F values (up to 8.5%), whereas a particle network assumes dominance at higher particle concentrations. 9 With surface treatment of CaSiO 3 , the app versus ␥ W plot exhibited a similar pattern to that of the i-PP/ CaSiO 3 system. However, the app data were lower than those for the corresponding untreated filler contents ( Figure 5).…”
Section: Apparent Melt Viscosity ( App )supporting
confidence: 59%
“…Thus, particle orientation predominates at low F values (up to 8.5%), whereas a particle network assumes dominance at higher particle concentrations. 9 With surface treatment of CaSiO 3 , the app versus ␥ W plot exhibited a similar pattern to that of the i-PP/ CaSiO 3 system. However, the app data were lower than those for the corresponding untreated filler contents ( Figure 5).…”
Section: Apparent Melt Viscosity ( App )supporting
confidence: 59%
“…For mica-filled PP [31] and various thermoplastics filled with calcium carbonate [202,261] it was shown that the relative viscosity of filled systems was lower than that of systems which contained equivalent quantitied of unfinished filler. Note that in contrast to viscosity in shear, the viscosity in stretching is higher for systems with treated filler [202].…”
Section: Effect Of Adhesion On Pcm Properties Property Control By Momentioning
confidence: 97%
“…At the same time, the strength of the composite, especially the impact strength, is lower in materials with agglomerates than in materials with a more uniformly distributed filler [30]. Treatment of fillers with modifying agents may also result in a situation where the system featuring a higher viscosity will have poorer strength characteristics [31,32].The shear viscosity, especially as measured with capillary rheometers characterized by high shear rates, is hardly sensitive to material structure since the investigator usually has to deal with the substantially destroyed structure in the molten sample. Melt stretching experiments would normally provide much more information [33].…”
mentioning
confidence: 99%
“…Dicumyl peroxide (DCP) was plasma, 7-9 titania coupling agent, 10 chlorinated obtained in commercial grade. The silane coupling paraffin, 11 silane coupling agent treatments, [12][13][14] agent, A-174, g-methacryloxy propyl trimethoxy and ultrasonic delamination. 15 In the area of rubsilane was supplied by Union Carbide (UK).…”
Section: Introductionmentioning
confidence: 99%